Mekanisme Molekuler Efek Hipolipidemik Senyawa Bioaktif dari Ekstrak Kulit Buah Alpukat (Persea americana Mill.) : Sebuah Kajian Literatur - Suwahyuni Mus; Nanik Sulistyani; Sapto Yuliani (Jurnal Penelitian Pendidikan IPA, 2026)
Avocado peel (Persea americana L.) contains a number of bioactive compounds that have the potential to act as antihyperlipidemic agents. These compounds include polyphenols, flavonoids, triterpenoids, phytosterols, and phenolic acids, which are known to affect lipid metabolism through various molecular pathways. This review aims to identify the molecular mechanisms underlying the antihyperlipidemic effects of avocado peel extract. Relevant literature was obtained through searches in the PubMed, Scopus, and Web of Science databases using relevant keywords. Selected studies were analyzed based on the PICO (Population, Intervention, Comparison, Outcome) framework and summarized using the PRISMA methodology. The results of the review indicate that avocado peel extract has the potential to activate the AMPK pathway, regulate PPAR-α/γ, inhibit HMG-CoA reductase, and increase bile acid excretion. However, most of the evidence is limited to animal models and in vitro studies, and further research in humans is needed to confirm the efficacy and to elucidate more in-depth molecular mechanisms.